Effect of processing parameters and void content on mechanical properties and NDI of thermoplastic composites. (June 2019) - Saenz-Castillo, D.; Martín, M.I.; Calvo, S.; Rodriguez-Lence, F.; Güemes, A.
Abstract: Several consolidation cycles were performed to study the impact of processing parameters on void content, ultrasonic NDT and mechanical performance of CF/PEEK composites. A series of [+45/−45]4S laminates were manufactured by out-of-autoclave technologies including vacuum bag only, hot-press, and automatic lay-up with in-situ consolidation. A range of porosity between 0 and 19% of void content was assessed by varying the processing temperature from 340 to 500 °C and pressure from 0.25 to 1.5 MPa. Void content, shape and location were characterized by using C-scan, matrix digestion and 2D microscopy. Mechanical characterization including in-plane shear and interlaminar shear testing was performed. The results show a critical void content where properties start to decrease at a given drop-off rate. The results suggest that each processing technology should have its own quality control criteria. The proposed methodology is useful for engineering applications of thermoplastic composites and the creation of NDT acceptance criteria.